KLF11 deficiency enhances chemokine generation and fibrosis in murine unilateral ureteral obstruction. - Silvana B De Lorenzo; Alyssa M Vrieze; Ruth A Johnson; Karen R Lien; Karl A Nath; Vesna D Garovic; Khashayarsha Khazaie; Joseph P Grande (PLoS ONE)
Progression of virtually all forms of chronic kidney disease (CKD) is associated with activation of pro-inflammatory and pro-fibrotic signaling pathways. Despite extensive research, progress in identifying therapeutic targets to arrest or slow progression of CKD has been limited by incomplete understanding of basic mechanisms underlying renal inflammation and fibrosis in CKD. Recent studies have identified Kruppel-like transcription factors that have been shown to play critical roles in renal development, homeostasis, and response to injury. Although KLF11 deficiency has been shown to increase collagen production in vitro and tissue fibrosis in other organs, no previous study has linked KLF11 to the development of CKD. We sought to test the hypothesis that KLF11 deficiency promotes CKD through upregulation of pro-inflammatory and pro-fibrogenic signaling pathways in murine unilateral ureteral obstruction (UUO), a well-established model of renal fibrosis. We found that KLF11-deficiency exacerbates renal injury in the UUO model through activation of the TGF-β/SMAD signaling pathway and through activation of several pro-inflammatory chemokine signaling pathways. Based on these considerations, we conclude that agents increase KLF11 expression may provide novel therapeutic targets to slow the progression of CKD.